Himenópteros parasitóides (Insecta, Hymenoptera) coletados em cultura de algodão (Gossypium hirsutum L.) (Malvaceae), no município de Ribeirão Preto, SP, Brasil - Nelson Wanderley Perioto; Rogéria Inês Rosa Lara; José Carlos Carvalho dos Santos; Aline Selegatto (Revista Brasileira de Entomologia, 2002)
Parasitoid Hymenoptera (Insecta, Hymenoptera) collected in a cotton (Gossypium hirsutum L.) (Malvaceae) plantation at the municipal district of Ribeirão Preto, SP, Brazil. Parasitoid Hymenoptera were collected by using Moericke trap placed in a cotton plantation (Gossypium hirsutum L.) of the variety Delta Pine 90, during the period of February 23rd to April 3rd, 2001. A total of 16,166 specimens of parasitoids, belonging to eight superfamilies and 22 families, were collected. Encyrtidae, Trichogrammatidae, Mymaridae and Scelionidae were the most common families, being responsible for 45.14%, 19.11%, 14.33% and 6.57% of the total number of parasitoids collected, respectively. Other eigthteen families showed the relative frequency lower than 5%.